TID characterised using joint effort of incoherent scatter radar and GPS - M. van de Kamp; D. Pokhotelov; K. Kauristie (Annales Geophysicae, 2014)
Travelling Ionospheric Disturbances (TIDs), which are caused by Atmospheric Gravity Waves (AGWs), are detected and characterised by a joint analysis of the results of two measurement techniques: incoherent scatter radar and multiple-receiver GPS measurements. Both techniques to measure TIDs are already well known, but are developed further in this study, and the strengths of the two are combined, in order to obtain semi-automatic tools for objective TID detection. The incoherent scatter radar provides a good vertical range and resolution and the GPS measurements provide a good horizontal range and resolution, while both have a good temporal resolution. Using the combination of the methods, the following parameters of the TID can be determined: the time of day when the TID occurs at one location, the period length (or frequency), the vertical phase velocity, the amplitude spectral density, the vertical wavelength, the azimuth angle of horizontal orientation, the horizontal wavelength, and the horizontal phase velocity. This technique will allow a systematic characterisation of AGW-TIDs, which can be useful, among other things, for statistical analyses. The presented technique is demonstrated on data of 20 January 2010 using data from the EISCAT incoherent scatter radar in Tromsø and from the SWEPOS GPS network in Sweden. On this day around 07:00–12:00 UT, a medium-scale TID was observed from both data sets simultaneously. The TID had a period length of around 2 h, and its wave propagated southeastward with a horizontal phase velocity of about 67 m s −1 and a wavelength of about 500 km. The TID had its maximum amplitude in Tromsø at 10:00 UT. The period length detected from the GPS results was twice the main period length detected from the radar, indicating a different harmonic of the same wave. The horizontal wavelength and phase velocity are also estimated from the radar results using Hines' theory, using the WKB approximation to account for inhomogeneity of the atmosphere. The results of this estimate are ...